A reduced graphene oxide/mixed-valence manganese oxide composite electrode for tailorable and surface mountable supercapacitors with high capacitance and super-long life. Issue 4 (22nd February 2017) - Wang, Yang; Lai, Wenhui; Wang, Ni; Jiang, Zhi; Wang, Xuanyu; Zou, Peichao; Lin, Ziyin; Fan, Hong Jin; Kang, Feiyu; Wong, Ching-Ping; Yang, Cheng
Abstract : The rGO/MnO x composite is compatible with the slurry dispensing process for electrode fabrication, and can exhibit super-long life property. Abstract : Developing supercapacitor electrodes with an ultra-long cycle life and a high specific capacitance is critical to the future energy storage devices. Herein, we report a scalable synthesis technology of mixed-valence manganese oxide nanoparticles anchored to reduced graphene oxide (rGO/MnO x ) as the high-performance supercapacitor electrodes. First, 2-dimensional (2D) δ-MnO2 nanosheets are formed on a graphene oxide (GO) template, which is then in situ reduced by hydrazine vapour to mixed-valence manganese oxide nanoparticles evenly distributed on a rGO conductive network. The obtained rGO/MnO x electrode material exhibits a high specific capacitance of 202 F g −1 (mass loading of 2 mg cm −2 ), a large areal specific capacitance of 2.5 F cm −2 (mass loading of up to 19 mg cm −2 ), and a super-long-life stability of 106% capacitance retention after 115 000 charge/discharge cycles. By using an ionic liquid electrolyte and an activated carbon anode, asymmetric supercapacitors (AScs) are also constructed and can be packaged into a high performance miniaturized energy storage component in either a tailorable or surface mountable configuration. Our ASc shows superior performance characteristics, with typical figures of merit including maximum energy densities of 47.9 W h kg −1 at 270 W kg −1 and 19.1 W h kg −1 at the maximum power density of 20.8 kW kg −1 . The capacitance retention of the ASc is 96% after 80 000 charge/discharge cycles, which is the most excellent stability performance in an ionic liquid electrolyte as compared with the recently reported pseudo-supercapacitors. This technology may find vast applications in future miniaturized portable and wearable electronics.